Pengelolaan Kemitraan Sekolah Menengah KejuruanDengan Dunia Usaha Dan Dunia Industri (Studi Kasus Pada SMK Muhammadiyah 2 Wuryantoro Kabupaten Wonogiri) - Ixtyarto, Bambang; , Dr. Suyatmini, M.Si; , Drs. Budi Sutrisno, M.Pd (2015)
The vocational education to build partnerships with industry will provide many advantages, including in developing the resources. Resource development intended here is for example through the use of the facility, as well as consulting and assistance through training activities. The form of other approaches that can be done between a vocational education with industrial world is in the form of partnership approach. The purposes of this study are 1) to describe the partnerships management planning of SMK Muhammadiyah 2 Wuryantoro with business and industrial world, 2) to describe the implementation of partnerships of SMK Muhammadiyah 2 Wuryantoro with business and industrial world, and 3) to describe the control implementation partnerships of SMK Muhammadiyah 2 Wuryantoro with business and industrial world. The research is a qualitative descriptive research. The design of this research refers to the ethnographic research. The research was conducted in SMK Muhammadiyah 2 Wuryantoro which is addressed in Jalan Melati No. 5, Wuryantoro, Wonogiri, Tel. (0273) 461448. This study focuses on the management of SMK Muhammadiyah 2 Wuryantoro partnerships with business and industrial world. The tecnique of data in this research is using field reearch technique. Data analysis used is an interactive analysis. The results of this study are the partnerships management planning in SMK Muhammadiyah 2 Wuryantoro done to manage potential schools in favor of cooperation with business and industrial world: a) Planning school promotion in establishing communication with business and industrial world, in the synchronization of the curriculum, prakerin students, graduate placement, teacher'son the job training place, b) Utilize the specific role of the business and industrial world a sa guest teacher, school funding, and scholarships, c) The business and industrial world cooperation outlined in the form of the MoU. The implementation of cooperation created MoU, the contents for the agreed areas of cooperation including validation and synchronization curriculum, industry visits, guests teacher, industry work practices, a vocational competency test (UKK), teacher on OJT ,certification, and recrutment/placement of graduates. The potential of the school include a teacher, the students and alumni have not been optimal, and not understanding the implementation of cooperation with business and ndustrial world. Majority the students are less the motivation to work and graduates have not been well-organized. The empowerment to support cooperate on with business and industrial world done bythe improvement and implementation of the work program of the school and the field of public relations programs.